Chapter Economic inequality in preindustrial Europe, 1300-1800: methods and results from the EINITE project - ALFANI, GUIDO (Datini Studies in Economic History, 2020)
This article provides an overview of the research done in recent years by the ERC-funded projects EINITE-Economic Inequality across Italy and Europe 1300-1800, and SMITE-Social Mobility and Inequality across Italy and Europe 1300-1800. It begins by discussing the sources available for reconstructing preindustrial economic inequality, especially in Italy, then it provides an overview of the methods which have been developed to produce reliable and homogenous information about inequality levels and trends. The method developed by EINITE to produce measures or distributions representative of broader aggregates (regions or entire states) is also discussed, as well as the techniques that can be employed to explore in a meaningful way such distributions to answer relevant historical questions.